Measurement Invariance of the Career Indecision Profile: United States and Iceland. (August 2013) - Abrams, Matthew D.; Ómarsdóttir, Anna Ó.; Björnsdóttir, María D.; Einarsdóttir, Sif; Martin, Colleen; Carr, Andrea; Brown, Steven D.; Rector, Christopher
This study explored the measurement equivalence of a recently developed multiscale measure of career indecision (Career Indecision Profile-65; CIP-65). Previous research had supported a four-factor structure of the CIP-65 in U.S. college students with factors appearing to measure (a) neuroticism/negative affectivity, (b) choice/commitment anxiety, (c) lack of readiness, and (d) interpersonal conflicts. The current study employed multiple groups confirmatory factor analyses to test whether the four CIP-65 factors are measured equivalently in the United States and Iceland. Results revealed that the four-factor structure fit both U.S. and Icelandic samples, but that two of the factors (choice/commitment anxiety and Interpersonal Conflicts might hold different psychological meanings in the two countries (i.e., factor loadings were not invariant). Some explanations for the lack of invariance in factor loadings are offered along with suggestions for future research and implications for practice.